2018
DOI: 10.1177/1558944718769665
|View full text |Cite
|
Sign up to set email alerts
|

Four-Strand Versus 2-Strand Suture-Button Constructs in First Carpometacarpal Arthroplasty: A Biomechanical Study

Abstract: The 4-strand and 2-strand suture-button constructs provide comparable biomechanical stability for first CMC arthroplasty. If construct stability is similar between these procedures, the smaller tunnel used with the 2-strand construct may offer an advantage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…28 He concluded that the effectiveness of these two techniques was comparable but emphasized the simplicity of HDA compared with the technical difficulty and cost of ligament reconstruction with tendon interposition, which can possibly lead to metacarpal fractures. 29 To our knowledge, no study has evaluated the effectiveness of distraction alone after early arthroscopic resection.…”
Section: Discussionmentioning
confidence: 99%
“…28 He concluded that the effectiveness of these two techniques was comparable but emphasized the simplicity of HDA compared with the technical difficulty and cost of ligament reconstruction with tendon interposition, which can possibly lead to metacarpal fractures. 29 To our knowledge, no study has evaluated the effectiveness of distraction alone after early arthroscopic resection.…”
Section: Discussionmentioning
confidence: 99%